The effect of training workshop on the knowledge and practices of pediatric oncology nursing in Syria: The effect of training workshop on the knowledge and practices of pediatric oncology nursing in Syria (Journal of Hama University, 2024)
Workshops are one of the basic keys to develop and improe the performance and efficiency of employees, by providing them the information and knowledge that they lack and developing of their abilities and skills. That in order to raise the level of efficiency, improve performance and increase productivity to the maximum possible quality. This is Why training is important as a key element in human resource development. The aim of this study is to know the effect of a training workshop on the information and skills of pediatric oncology nursing in several hospitals in Syria.A study was Experimental on sample consisting 121 nurses, through the Basma Association for Children suffering from Cancer and with the support of World Health Organization. The information of 121 nurses was evaluated before and after the workshop through a questionnaire that included the information basic knowledge of pediatric tumors, and training them on the skill of washing and sterilizing hands, in addition to the skill of installing the central porta catheter, then evaluate the nursing performance of skills after doing the workshop.The result of the study showed the total mean of information of nurses in Syria before the workshop was 57.6, When the result was after doing the workshop 80.77. Thus, the computed value of t is
Keywords: pediatric oncology, training workshop.